Real-world results of first-line ABVD in patients with classic Hodgkin's lymphoma at a neoplastic disease institute in Lima, Peru - Salinas Agramonte, Luis Andre (2025)
Objective: To evaluate the clinical characteristics and outcomes of first-line ABVD (doxorubicin, bleomycin, vinblastine, dacarbazine) in patients with classical Hodgkin lymphoma treated at a neoplastic disease institute in Lima, Peru. Methods: Retrospective study of previously untreated classical Hodgkin lymphoma diagnosed between 2014 and 2018. All received ABVD days 1 and 15 every 28 days. We described clinical features, objective response rate (ORR), overall survival (OS), and adverse events (AEs) per CTCAE v5.0, and explored associations between clinical variables and response using the chi-square test. Results: A total of 157 patients were included, with a median age of 31.5 years (interquartile range [IQR]: 22–49.25), of whom 56.7% were male. The most common histological type was nodular sclerosis (64.3%). Bulky disease was present in 17.8%, mediastinal mass in 45.2%, and B symptoms in 76.4%. Disease stages were distributed as follows: stage I (5.1%), stage II (36.9%), stage III (34.4%), and stage IV (22.9%). The complete response (CR) rate was 97.1%. Over the 36 months, overall survival (OS) was 83.1%. Regarding toxicity, grade 3–4 neutropenia occurred in 31.8%, while the most frequent non-hematological toxicity was nausea (24.8%). Conclusions: In this cohort, first-line ABVD showed effectiveness with a toxicity profile comparable to prior reports, supporting its use in resource-limited settings. Optimizing supportive care and incorporating PET/CT may help refine treatment selection and follow-up.